Assessment of salat taraweeh and fasting effect on body composition - Mohktar, M.S.; Ibrahim, F. (2008)
This paper presents the changes in the body composition on 18 male Muslim subjects during salat taraweeh and fasting in the month of Ramadhan. Body composition is measured by using single frequency bioelectrical impedance analysis (BIA). The measurement is performed on 30 Sya'aban (baseline measurement) and 19th of Ramadhan (final measurement). The body composition results showed that after 20 days of fasting and taraweeh, the mean value of phase angle (PA), basal metabolic rate (BMR), lean body mass (LBM), and the ratio of total body water to total weight (TBW/TW) increased significantly (p<0.05) meanwhile, the resistance, fat mass (FM) and glucose values decreased significantly (p<0.05). These changes indicate that salat taraweeh dan fasting give a good improvement to the body composition and overall health. Â© 2008 Springer-Verlag.